Aggregate licenses validation for digital rights violation detection - Kankanhalli, Mohan S. (2013)
Digital Rights Management (DRM) is the term associated with the set of technologies to prevent illegal multimedia content distribution and consumption. DRM systems generally involve multiple parties such as owner, distributors, and consumers. The owner issues redistribution licenses to its distributors. The distributors in turn using their received redistribution licenses can generate and issue new redistribution licenses to other distributors and new usage licenses to consumers. As a part of rights violation detection, these newly generated licenses must be validated by a validation authority against the redistribution license used to generate them. The validation of these newly generated licenses becomes quite complex when there exist multiple redistribution licenses for a media with the distributors. In such cases, the validation process requires validation using an exponential number (to the number of redistribution licenses) of validation inequalities and each validation inequality may contain up to an exponential number of summation terms. This makes the validation process computationally intensive and necessitates to do the validation efficiently. To overcome this, we propose validation tree, a prefix-tree-based validation method to do the validation efficiently. Theoretical analysis and experimental results show that our proposed technique reduces the validation time significantly.